PENGUJIAN KABEL TEGANGAN TINGGI XLPE DENGAN MENGGUNAKAN TEKNIK AFTER LAYING - Abduh, Syamsir (Jurnal Teknik Elektro, 2004)
Power system equipment must withstand not only the rated voltage which corresponds to thehighest voltage of a particular system but also over-voltages. Accordingly, it is necessary totest high voltage equipment stage and prior to commissioning. The magnitude and type oftest voltage varies with the rated voltage of particular apparatus. The standard methods ofmeasurement of high voltage and the basic techniques for application to all type ofapparatus for alternating voltage, direct voltage, partial discharge (well known as afterlayingtest) are aid down in the relevant application such as XLPE underground cable.Keywords: After Laying, XLPE Cable